Inventory of brownfield sites in Slovenia : towards a new methodology = Popis brownfield lokacija u Sloveniji : prema novoj metodologiji - Cotič, Boštjan (Array, 2020)
The paper compares methods and results concerning the two most recent inventories of brownfield sites in Slovenia: while the MOP inventory focuses more on spatial planning issues, the MGRT inventory concentrates more on economic issues. Therefore, the two methodologies used cannot be properly combined and a new methodology for brownfields inventory is only able to adopt certain elements of each.